Morfologia integrativa e revisão taxonômica de populações brasileiras de "Chaetonotus polyspinosus" Greuter, 1917 (Gastrotricha: Chaetonotida: Chaetonotidae) : Integrative morphology and taxonomy of brazilian populations of "Chaetonotus polyspinosus" Greuter, 1917 (Gastrotricha: Chaetonotida: Chaetonotidae) - Andrade, Patrícia Pereira de, 1993- (2020)
Orientador: André Rinaldo Senna Garraffoni